Equine Protozoal myeloencephalitis of acute onset: Case Report - Ribeiro Faria, Thalita Tainá Ribeiro Faria; Oliveira Pessoa, Gabriela; Arrais Biihrer, Daniel; de Pádua Lima, Antonio; Varaschin, Mary Suzan; Meireles Sousa, Ticiana (Pubvet, 2017)
A case of Equine Protozoal Myeloencephalitis caused by Sarcocystis neurona, was treated at the Veterinary Hospital of the Federal University of Lavras-MG. Among the neurological disorders in horses EPM is one of the most frequent and major economic losses in equideocultura. The animal in question showed symptoms acutely, with decubitus, reduction of superficial and deep skin sensitivity, loss of tail tone, facial nerve injury and urinary incontinence. The diagnosis was based on clinical symptoms, necropsy and the protozoan associated to the microscopic lesions. The treatment used was diclazuril corticoideterapia and treatment support.